2020
DOI: 10.22271/j.ento.2020.v8.i1aa.6372
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of whitefly (Bemisia tabaci Genn.) infesting BT cotton and their insecticidal management under field conditions

Abstract: Studies were taken up to monitor the seasonal occurrence of whitefly population in cotton as well as its insecticidal management under field conditions of Institutional Research Farm, Institute of Agriculture, Visva-Bharati, Sriniketan, during the kharif season of 2018-19. Population reduction of whitefly was done with eight insecticides having different molecular composition and one untreated check. The experiment was drawn in a Randomised Block Design with three replications. The occurrence of whitefly was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…(2019) [3] who reported that maximum activity of whiteflies (4.50 whiteflies/leaf) was observed during the 39 th MW. Similarly, Pal et al (2020) [15] revealed that the occurrence of whitefly was noticed during the fourth week of July (0.20 whitefly/plant) which continued till late December.…”
Section: Whitefly (Bemisia Tabaci)mentioning
confidence: 82%
“…(2019) [3] who reported that maximum activity of whiteflies (4.50 whiteflies/leaf) was observed during the 39 th MW. Similarly, Pal et al (2020) [15] revealed that the occurrence of whitefly was noticed during the fourth week of July (0.20 whitefly/plant) which continued till late December.…”
Section: Whitefly (Bemisia Tabaci)mentioning
confidence: 82%
“…Asif et al (2016) reported that imidacloprid and lambda cyhalothrin were effective against cotton sucking pests. Pal et al (2020) reported that combination product of imidacloprid 6% + lambda cyhalothrin 4%SL @ 500 ml/ha and 450 ml/ha proved the most effective in Bt cotton. Significantly highest seed cotton yield was recorded in the plots treated with imidacloprid 6%+ lambda cyhalothrin 4% SL @ 500 ml ha -1 and was on par with its lower doses at 450ml/ ha and 400 ml/ ha -1 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…As per Sharma et al (2017), the peak population of the whitefly on tomatoes was attained during the 21 st standard meteorological week and the correlation studies showed that the whitefly population was positively correlated with the temperature and sunshine, while a negative correlation was observed with the humidity and rainfall. Subba et al (2017) concluded, from a trail, that the peak level was found during the 11 th to 18 th standard week with the highest population of (0.47/leaf ) recorded at a temperature of 28.80-27.42 °C, a relative humidity of 92.46 to 75.59% and rainfall of 8.80 to 240.00 mm, whereas Deb and Bharpoda (2017) recorded that the incidence started from the 39 th SMW (4 th week of September) and the population represented peaks during the 45 th SMW (1 st week of November) with a population of 2.72 whiteflies/3 compound leaves and 48 th SMW (4 th week of November). Wade et al (2020), from the research, revealed that the whitefly was first noted during the 2 nd SMW on tomatoes along with a peak population level of 7.83 whiteflies per three leaves during the 16 th SMW, while, according to Kachave et al (2020), the whitefly population commenced from the 31 st SMW to the 47 th SMW (30 th of July to 22 th of November) and recorded a maximum and minimum temperature of 34.4 and 18.00 °C, morning and evening relative humidity of 74% and 27%, 6 mm of rainfall and 7.4 hours of sunshine.…”
Section: Whitefly B Tabacimentioning
confidence: 99%